Noninvasive Imaging Biomarkers of Vulnerable Coronary Plaques – a Clinical Update - Mitra Noémi; Cernica Daniel; Hodas Roxana; Chițu Monica; Kovács István; Raț Nóra; Benedek Imre (Journal of Interdisciplinary Medicine, 2019)
Atherosclerosis is a slow, progressive disease, its most common manifestation and most severe consequence being coronary artery disease, one of the main causes of mortality and morbidity worldwide. The vast majority of cardiovascular deaths are caused by complications of atherosclerosis, most often being represented by the rupture of an unstable coronary plaque, regularly triggered by inflammation. A vulnerable plaque is characterized by a large, lipid-rich necrotic core, a thin fibrous cap with macrophage infiltration, and the presence of multiple specific biomarkers such as positive remodeling, irregular calcifications, and low attenuation visible with coronary computed tomography angiography (CCTA). Identifying biomarkers that could predict the risk of plaque rupture with high accuracy would be a significant advance in predicting acute cardiac events in asymptomatic patients, furthermore guiding treatment of patients with this disease. The main indication of noninvasive imaging is to identify patients at risk based on the presence or absence of symptoms that can be related to myocardial ischemia. The diagnostic objective is to confirm or to exclude the presence of coronary plaques. Coronary imaging in asymptomatic individuals is used to estimate the risk of future cardiac events through the identification of non-obstructive high-risk plaques. The possibility to monitor the evolution of vulnerable plaques via noninvasive imaging techniques, prior to the occurrence of an acute clinical event, is the main goal in plaque imaging. This manuscript will be focusing on recent advances of noninvasive imaging of vulnerable coronary plaques.